The Machine is Us/ing Us - Wesch, Michael (My University, 2010)
"Web 2.0" in just under 5 minutes. This video was released on YouTube on January 31st 2007 and quickly became the most popular video on the web throughout February 2007. The song is "There’s Nothing Impossible" by Deus.
Keywords: Web 2.0; Hypertext; XML; HTML